Pathogenicity Assay of Vibrio harveyi in Tiger Shrimp Larvae Employing Rifampicin-Resistant as A Molecular Marker - Widanarni, .; Meha, D.; Nuryati, Sri; Sukenda, .; Suwanto, A. (Indonesian Society of Scientific Aquaculture (ISSA), 2004)
Rifampicin-resistant marker was employed as a reporter to assay pathogenicity of Vibrio harveyi in shrimp larvae. V. harveyi M. G3 and G7 that difference not schizotyping as shown by Pulsed-Filed Gel Electrophoresis (PFGE) used in this study. Spontaneous mutation was conducted to generate V. harveyi resistant to rifampicin. Two groups of shrimp post-larvae (PL5) were immersed for 30 min in 106 CFU/ml of mutants and wild type of V. harveyi, respectively; and then placed in a 2 liter shrimp rearing tank for five days. A control group was immersed in sterile seawater. Growth curve analysis and pathogenicity assay of V. harveyi showed that each of the V. harveyi mutant exhibited almost identical profiles to that of the wild type parental strain and did not show alteration in their pathogenicity. Sample from dead shrimp larvae showed that the dead shrimp larvae were infected by V. harveyi RfR, indicated that rifampicin-resistant marker effective as a reporter to assay pathogenicity of Vibrio harveyi in shrimp larvae. Key words: shrimp larvae, Vibrio harveyi, rifampicin-resistant, molecular marker